Features of forced migration flows of ukrainians under temporary protection in the European Union: the case of Romania - Gavrikova, Iryna; Kravchenko, Kateryna (Human Geography Journal, 2025)
The article examines the specific features of the formation and development of forced migration flows of Ukrainian citizens under temporary protection in the countries of the European Union, using Romania as a case study. The regulatory and legal foundations of the temporary protection mechanism are analysed, and a comparative assessment with the institution of asylum is conducted, which makes it possible to identify differences in legal status and social consequences for displaced persons. Based on statistical data, the dynamics of the number of Ukrainian nationals who have benefited from this mechanism, as well as their age and gender structure, are examined. It is revealed that in the first years of the full-scale war women and children predominated, whereas in 2023–2024 the share of working-age persons increased, indicating a transformation of migration from predominantly humanitarian to socio-economic. It is substantiated that these shifts have significant demographic implications for Ukraine: the outflow of women of reproductive age and children leads to declining birth rates and intensifies the risks of demographic decline, while the emigration of the working-age population complicates the prospects for restoring labour potential.The specific features of the Romanian response model are outlined, which combines emergency humanitarian assistance with measures aimed at social integration and facilitating access to the labour market. It is demonstrated that temporary protection for Ukrainian citizens in EU countries functions not only as an instrument of rapid response to a humanitarian crisis but also as a factor of deeper socio-economic and demographic transformations. Particular attention is paid to the territorial patterns of settlement of Ukrainians across different regions of Romania. Further research is expected to focus on a comparative analysis of the experience of other EU Member States in order to develop generalised conclusions and practical recommendations for the migration policies of Ukraine and the European Union.